Adenosine-sensitive atrial tachycardia originating from the para-Hisian region with a slow conduction zone in the anteroseptal left atrium. Issue 2 (August 2021) - Sakai, Satoshi; Takitsume, Akihiro; Kawata, Hiroyuki
Abstract: Adenosine-sensitive atrial tachycardias (ATs) originating from the para-Hisian region have been reported, and the responsible mechanism is considered to be reentry. As an alternative strategy to ablation at the earliest activation site (EAS) close to the atrioventricular node, previous reports safely eliminated these ATs at the entrance of the slow conduction zone, indicated by a manifest entrainment-guided strategy, but no report has successfully ablated those ATs using the same strategy in the left atrium. We describe a case of adenosine-sensitive AT originating from the para-Hisian region that could be eliminated at a remote site from the EAS indicated by the demonstration of manifest entrainment from the high anteroseptal left atrium. <Learning objective: Previous reports safely eliminated adenosine-sensitive atrial tachycardias (ATs) originating from the vicinity of the atrioventricular (AV) node at the entrance of the slow conduction zone (SCZ), indicated by a manifest entrainment-guided strategy. There may be cases with the SCZ in the left atrium (LA), but radiofrequency application on the anteroseptum of the LA near the AV annulus has a potential risk of causing an AV block. Therefore, that strategy in the LA can be a reasonable option.>